JBPM6 developer guide : learn about the components, tooling, and integration points that are part of the JBoss Business Process Management (BPM) framework /: learn about the components, tooling, and integration points that are part of the JBoss Business Process Management (BPM) framework. (2014) - De Maio, Mariano Nicolas; Salatino, Mauricio; Aliverti, Esteban
No abstract available